Kepintaran Emosi Di Kalangan Guru Sekolah Menengah Di Daerah Kota Setar - Nordien, Sulaiman (2001)

(untitled)
Emotional intelligence (EQ) exerts significant influence ini the career of a teacher who always finds himself in front of a class of pupils.The ability to practice emotional intelligence aEectively will create an atmosphere of harmony between the teacher and his pupils. This will bring about positive effects on his teaching and learning. Owing to the importance of emotional intelligence servey is carried out to study the level of emotional intelligence among secondary school teachers in the district of Kota Setar ini Kedah Darul Aman. A total of 330 respondents from six schools were randomly selected. A questionaire was used to collect data which was then analysed using the Statistical Package for the Social Science (SPSS) method. The findings of the survey recalled that the majority of the respondents displayed a high level of emotional intelligence. The respondents were knowledgeable in their respective fields (subjects) and were able to put into practice all the components of emotional intelligence, namely, managing emotions, emotional awareness of others, self - motivation and establishing relationships. However, the results showed an absence of any significant relationship between demographic factors and emotional intelligence in general.